Estimating the CPU utilization of a rule-based system. - Avritzer, Alberto (Software engineering notes.)
Rule-based software systems have become very common in telecommunications settings, particularly to monitor and control workflow management of large networks. At the same time, shorter deployment cycles are frequently necessary which has led to modifications being made to the rule base, without a full assessment of the impact of these new rules through extensive performance testing.An approach is presented that helps assess the performance of rule-based systems, in terms of its CPU utilization, by using modeling and analysis. A case study is presented applying this approach to a large rule-based system that is used to monitor a very large industrial telecommunications network.